Correlation of moisture content and heating value of refuse-derived fuel - Nur Anis Yasira, Abd Halim; Noor Intan Shafinas, Muhammad (IOP Publishing, 2025)
Refused Derived Fuel (RDF) from mixed agricultural residues (AgResidue) is a potential solution to reduce coal dependency due to its similar energy content. This study aims to determine the correlation between moisture content and heating value (HHV) of five RDF formulations containing PKS, CS, CH, and EFB, with varying moisture content (MC) levels of 5%, 8%, and 10%. The results demonstrated that all samples showed an increase in HHV as the moisture content decreased, as more water content absorbs energy during burning, leading to a decrease in net output. These findings highlight the critical importance of reducing moisture content in RDF to enhance energy output, demonstrating the effectiveness of drying techniques or moisture control methods.